Spiritual Care Dalam Mengurangi Tingkat Kemarahan Pasien Skizofrenia - Mohammad Risky Baisoeni; Maulidiyah Junnatul Azizah; Atika Jatimi; Zainal Munir; Handono Fatkhur Rahman (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Patients with schizophrenia tend to have high emotional levels, which has the potential to increase the risk of violent behavior. The existence of spiritual interventions that are used bring benefits in the form of increasing its capacity to overcome suffering and to overcome life's problems, as well as accelerate healing in addition to medical care provided. Methods: The method used in this article was a literature review. Literature sources used in the preparation of this study using journal articles from 2015-2020. The process of finding articles through Proquest, EBSCO, DOAJ, Geogle scholars, and Research Gate. There were 20 articles relating to spiritual care to reduce the level of anger in schizophrenic patients. Results: The results of this study indicate that to reduce the risk of anger, many nursing interventions are used. The results of several particles that have been tracked, there are spiritual therapies that can be done by providing intervention to schizophrenic patients such as meeting spiritual needs with prayer, prayer, remembrance, prayer, reading the Koran, murrotal therapy, ruqyah and attention to therapy with a spiritual approach. Conclusion: Spiritual treatment has the effect of reducing the anger level of schizophrenic patients. The most widely used method is remembrance, therefore, there are other methods, namely by way of prayer, eating pork, reading the Koran, lectures, murrotal, and ruqya shar'yyab therapy. These methods are very influential on many things, ranging from reducing the level of anger, reducing the risk of violent behavior, reducing hallucinations, and also as a patient's self control. Keywords: spiritual; angry; schizophrenia ABSTRAK Latar Belakang: Pasien dengan skizofrenia cenderung memiliki tingkat emosi yang tinggi, yang berpotensi meningkatkan risiko perilaku kekerasan. Adanya intervensi spiritual yang digunakan membawa manfaat dalam bentuk meningkatkan kapasitasnya untuk mengatasi penderitaan dan untuk mengatasi masalah kehidupan, serta mempercepat penyembuhan di samping perawatan medis yang diberikan. Metode: Metode yang digunakan dalam artikel ini adalah tinjauan literatur. Sumber literatur yang digunakan dalam penyusunan penelitian ini menggunakan artikel jurnal dari 2015-2020. Proses menemukan artikel melalui Proquest, EBSCO, DOAJ, Google Scholar, dan Research Gate. Ada 20 artikel yang berkaitan dengan perawatan spiritual untuk mengurangi tingkat kemarahan pada pasien skizofrenia. Hasil: Hasil penelitian ini menunjukkan bahwa untuk mengurangi risiko kemarahan, banyak intervensi keperawatan digunakan. Hasil dari beberapa partikel yang telah dilacak, ada terapi spiritual yang dapat dilakukan dengan memberikan intervensi kepada pasien skizofrenia seperti memenuhi kebutuhan spiritual dengan doa, sholat, zikir, sholat, membaca Alquran, terapi murrotal, ruqyah dan perhatian terhadap terapi dengan pendekatan spiritual. Kesimpulan: Spiritual care memiliki pengaruh untuk menurunkan tingkat kemarahan pasien skizofrenia. Adapun metode yang paling banyak digunakan adalah berdzikir, kemudian, ada metode lain yaitu dengan cara berdoa, beristigfar, membaca al-quran, ceramah, murrotal, serta terapi ruqya syar’iyyab. Kata Kunci: spiritual; kemarahan; skizofrenia